KETERKAITAN KETERBUKAAN KOMUNIKASI, PENGHARGAAN DARI PIMPINAN, DAN PARTISIPASI PEGAWAI TERHADAP KINERJA PEGAWAI - Dede Aisyah (Faculty of Economics and Business Diponegoro University, 2015)
This research was conducted at the Department of Revenue Office South Lampungregency from November to December 2002 order to determine the canonical correlationbetween: (1) Implementation of human relations on morale and performance ofemployees and (2) further to determine the correlation between the three sub-variables ofhuman relations: (a) communication openly, (b) award the leadership and (c) theparticipation of employees in 3 subvariable activities on employee performance, namely:(i) the discipline of work, (ii) attitude cooperation and (iii) the productivity of employees.Data collection is done using questionnaires to 43 staff these offices. each sub variablepoured into 3 questions with 3 choices of answer ordinal scale. Scoring data is done by:the answers are very in line with expectations given a score of 3, in line with expectations2, and is not suitable with expectations given a score of 1. Correlation analysis used isthe analysis canonical correlation (canonical correlation analysis) using the tool SAS(Statistical Analysis System) Program Version 6:12 with using the likelihood ratio test ona real level = 0.05 and 0.10. Conclusion which can be made from this study are: (1) thereis a real connection between human relations with employee performance and more (2)no real connection Among the sub-variables of human relations that opencommunication, leadership awards and employee participation in the activities of theinstitution labor discipline, but not real terhdap cooperation attitude of employees, andonly appreciation leaders who have real correlation to productivityemployees.Keywords: human relations, open communication, employee performance.